The Effect of Acupressure Therapy on Blood Pressure Reduction in Hypertensive Patients in the Working Area of UPTD Puskesmas Loji, Majalengka Regency - Al Farez, M.Fahad; Muadi, Muadi; Dwi Andhini, Citra Setyo (Jurnal Kesehatan Mahardika, 2025)
The main cause of premature death worldwide is referred to as High Blood Pressure or Hypertension. One way to address hypertension is through Acupressure therapy. This study aims to examine the effect of acupressure therapy on lowering high blood pressure in individuals with hypertension. The study utilizes a Quasi-Experimental research design with a Pre-test – Post-test Without Control approach, with a Non-Probability Sampling method using Purposive Sampling, involving 94 elderly individuals with hypertension. Blood pressure was measured using a sphygmomanometer and acupressure therapy was applied following Standard Operating Procedures (SOP). The results of the study show that before acupressure therapy, the average systolic and diastolic blood pressure was 156.62/103.64 mmHg, while after the therapy, the average systolic and diastolic blood pressure dropped to 146.72/97.23 mmHg, showing a significant decrease. The mean rank of systolic and diastolic blood pressure before therapy was 47.50, while after therapy, the mean rank dropped to 0.00. A p-value of 0.001 < 0.05 indicates that this difference is statistically significant, meaning that acupressure therapy has a significant effect on lowering blood pressure in individuals with hypertension in the working area of the Loji Health Center.